2022
DOI: 10.3389/fpsyt.2022.882491
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Perspectives in the Immune Therapy for Substance Use Disorders

Abstract: Substance use disorders (SUDs) are an extremely challenging category of disorders because of the high rate of relapse, lower life expectancy, important rate of psychiatric and somatic co-morbidity, lack of patients' insight during most of the disease duration, healthcare costs, etc. One of the reasons to consider these disorders very difficult for physicians and the healthcare system is the lack of adequate pharmacological agents with long-term proven efficacy. So far, there are no Food and Drug Administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In conclusion, the necessity of investigating the available treatments for B/SD is derived from multiple factors: the use of excessive buying as a way to cope with stress or isolation ( 27 ); negative functional consequences and risk of a chronic course ( 28 ); and the relatively high and increasing prevalence of problematic buying in the general population ( 1 , 16 ). The need to assess the efficacy of psychotherapeutic, pharmacological and combined therapies in BAs or SUDs is also motivated by the high societal and personal costs associated with healthcare in B/SD, high risk of psychiatric or somatic comorbidity, and lower quality of life ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the necessity of investigating the available treatments for B/SD is derived from multiple factors: the use of excessive buying as a way to cope with stress or isolation ( 27 ); negative functional consequences and risk of a chronic course ( 28 ); and the relatively high and increasing prevalence of problematic buying in the general population ( 1 , 16 ). The need to assess the efficacy of psychotherapeutic, pharmacological and combined therapies in BAs or SUDs is also motivated by the high societal and personal costs associated with healthcare in B/SD, high risk of psychiatric or somatic comorbidity, and lower quality of life ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…While significant progress has been made in understanding the neurobiology and behavioral aspects of addiction, the development of targeted medications has proven challenging. So far, there is no drug treatment approved by the FDA (Food and Drug Administration) or EMA (European Medicines Agency) for most substance use disorders, except for AUD (Alcohol Use Disorder), NUD (Nicotine Use Disorder), and OUD (Opioid Use Disorder) [26].…”
Section: Pharmacology and Treatment Insights On Sudmentioning
confidence: 99%
“…No FDA-or EMA-approved drug treatment for most substance use disorders [26] Lack of officially approved pharmaceutical treatments for most substance use disorders.…”
Section: Pharmacology and Treatmentmentioning
confidence: 99%
“…The excessive use of alcohol may affect GM in human and animal models, leading to a dysbiosis that can represent an essential link in the pathogenesis of alcohol use disorders (AUD). Most of the data regarding this subject are derived from animal studies, which showed a connection between chronic alcohol use and increased oxidative stress, higher intestinal permeability to different bacteriaproduced toxic factors, and the onset of alcoholic hepatitis (2,74). Increased dysbiosis may determine systemic inflammation and endotoxemia, as well as specific organ pathologies, supporting, at a theoretical level, the usefulness of a probiotic or synbiotic modulation of the GM as prophylactic measures or therapeutic interventions in AUD (2).…”
Section: Substance Use Disordersmentioning
confidence: 99%